MULTIVARIATE CUSUM CONTROL CHART BASED ON THE RESIDUALS OF MULTIOUTPUT LEAST SQUARES SVR FOR MONITORING WATER QUALITY - Khusna, Hidayatul; Mashuri, Muhammad; S., Suhartono; Prastyo, Dedy Dwi; Ahsan, Muhammad (Malaysian Journal of Science, 2019)
Monitoring serially dependent processes using conventional control charts yields a high false alarm rate. Multioutput Least Squares Support Vector Regression (MLS-SVR) has the capability to encompass the cross-relatedness between output variables by learning multivariate output variables simultaneously. This research aims to develop a Multivariate Cumulative Sum (MCUSUM) control chart based on the residual obtained from the MLS-SVR model for monitoring autocorrelated data. The inputs of the MLS-SVR are selected using the significant lag of a partial autocorrelation function. The proposed control chart is applied to monitor water quality data and it can detect the assignable causes in those data caused by a broken pipeline.